Design Analysis and Structural Prediction of Bus Driver Chair Support: A Study Case using HOQ and FEM - Cho, Joung Hyung; Ridwan, Ridwan; Kusuma, Rama Panji; Triyono, Joko; Muhayat, Nurul; Fajri, Aprianur; Laksono, Fajar Budi (Mekanika: Majalah Ilmiah Mekanika, 2023)
The bus driver's comfort is crucial. The location of the driver's seat, which is correlated with the seat support design, is one of the elements supporting his comfort. By considering the safety factor, House of Quality (HOQ), weight, shape, and seat support dimensions, this study intends to ascertain how the characteristics of the bus seat support form after receiving a load or force. Conducting a field visit to gather the necessary data was the initial step in this research. The following stage was to decide on the design criteria based on the collected data. Next, use SolidWork to model the design. Using the Finite Element Method (FEM), this program can investigate design characteristics. The loading simulation under consideration included clutch engagement, bus brake application, and clutch engagement, whether the support was static or stationary. The validation with two supporting journals was then run as the following step to validate the findings. According to the study's findings, the constant chair support fulfills the typical value, whereas Support 1 was the most fracture-prone. The outcomes of Supports 2 and 3 demonstrated that the support strength was weak since it was subjected to an unequal load.